Phytochemical Constituents and In vitro Pharmacological Response of Cnidium monnieri; A Natural Ancient Medicinal Herb. Issue 3 (17th August 2022) - Munir, Naveed; Mehmood, Zahed; Shahid, Muhammad; Aslam, Samina; Abbas, Mazhar; Mehboob, Huma; Al-Mijallia, Samiah H.; Jahangeer, Muhammad; Badar, Qurrat ul Ain
Background: Natural medicines are being used for the treatment of various disorders due to pharmacological, therapeutical, and nutraceuticals characteristics. Objectives: Current research was planned to explore In vitro pharmacological response of phytochemical constituents extracted from C. monnieri' seeds using aqueous ethanol (70%). Methods: Qualitative and quantitative measurements for phytochemical constituents were performed following reference protocols. Then In vitro antioxidant potential, cytotoxic studies, antimicrobial, and spermicidal pharmacological response of C. monnieri extract were investigated. Results: The results of High Performance Liquid Chromatography (HPLC), Fourier Transform Infra-Red (FTIR) spectroscopy, and Atomic Absorption Spectrophotometer (AAS) explored the presence of wide range of bioactive compounds with significant (p<.05) antioxidant activities. Cytotoxic studies revealed significant (p<.05) protective behavior of C. monnieri evaluated using CtDNA damage protection, against Salmonella typhi TA98 and TA100, RBCs membrane stabilizing and clot lysis assay. It was also found that selected herb has antibacterial and antifungal activities. The results of spermicidal study on human (n = 30) spermatozoa revealed significant (p<.05) contraceptive per vaginal behavior of this natural medicinal plant. Conclusion: It could be concluded that C. monnieri showed significant pharmacological activities with non-toxic behavior, however In vivo study in animals and clinical trials are required to declare this natural herb as therapeutic agent.